Optimizing Visual Identity City Branding Grobogan Through Design Thingking Approach Based on Cakra Manggilingan Concept - Romadhon, Mohammad Aditia Gilang; Yunianto, Ipung Kurniawan (Gondang: Jurnal Seni dan Budaya, 2025)
Grobogan Regency is building a positive image and promoting the region's superior potential through the Javanese philosophy concept "Cakra Manggilingan" which is manifested in the visual identity of the city branding "The Miracle of Charm". Cakra Manggilingan which means the rotating cycle of life and the balance of nature, is represented in the visual identity of the city branding to illustrate the dynamics and potential of Grobogan which continues to grow. This study aims to analyze and describe the meaning of the symbol and tagline "The Miracle of Charm" in the visual identity of the city branding of Grobogan with the Design Thinking approach. This approach was chosen to understand the needs and aspirations of the community (empathize), formulate problems (define), develop innovative idea concepts (ideate), create a prototype of the visual identity of the city branding (prototype), and test the effectiveness of the design (test). The descriptive qualitative research method was used with data collection techniques in the form of interviews, questionnaires and literature studies. The results of the analysis show that the design of the city branding logo uses visual elements, namely leaves, corn, the Kender mountains, water flow, the eternal fire of Mrapen, and Boyong Grobog to represent the diversity of Grobogan's potential in terms of tourism, social, culture, religion, culinary, and agribusiness. The tagline "The Miracle of Charm" strengthens and unites the previous taglines that reflect the magic and charm of Grobogan which comes from the harmony between nature, culture, and its people